EFFICACY OF ORAL VORICONAZOLE VERSUS ORAL ITRACONAZOLE, IN THE TREATMENT OF DERMATOPHYTE INFECTIONS - Ali, Maira; Najia Ahmed,; Seemab Khan,; Afshan kiran, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Dermatophyte infections are common in tropical areas with a humid climate. In recent times, it is getting extremely challenging to treat these infections because of resistance that has occurred to the conventional antifungals, which is attributed to changes in the fungal strains. Keeping in view this issue, more advanced drugs have come into being. Voriconazole is a potential such drug with promising results. Methods: A total of 76 patients participated in the study, they were divided into two groups, with 38 participants in each group. Group A was treated with voriconazole and group B was treated with itraconazole, for 2 weeks in patients who achieved a complete response, and 4 weeks for patients who achieved a partial response. Baseline complete blood count, Liver function tests, renal function tests, blood sugar levels, and KOH microscopy was done for every patient, and was repeated after completion of treatment. Clinical response was assessed on the basis of clearance of the lesion and negativity on KOH microscopy. Results: After completion of treatment with voriconazole, 32 (84.2)% of the patients achieved a complete clearance of the lesion, while 6(15.8%) of the participants achieved partial response to the treatment. Among the patients who received oral itraconazole,6 (15.7%) showed a complete response ,16 (42.1%) participants achieved a partial cure, while 16 (42.2%) patients did not show any improvement after the treatment. Conclusion: It is safe to conclude, that voriconazole shows better efficacy and results in treating resistant dermatophyte infections.